Prevalence of Congenital Heart Defects and their Non-Inherited Risk Factors among Children through the Period 2019-2023: A Retrospective Comparative Study - Abd Ali, Maryam Eid; Qasim, Nuhad Mouhammed (International Journal of Child Health and Nutrition, 2024)
Background: Congenital heart defects (CHD) are the most common types of congenital disabilities. The frequency of CHD among their patient populations also remains the leading cause of their increased mortality, accounting for an estimated 50% of all causes of death from abnormalities. Objectives: The study aimed to identify the prevalence of non-inherited risk factors among children with cardiac defects and compare the prevalence of congenital heart defects among children in different governorates in Iraq related to non-inherited risk factors. Materials and Methods: A retrospective study design was used to study congenital heart defects in children in Babylon Centre for Catheterization and Cardiac Surgery in Al-Imam Sadiq Hospital Babylon province, Iraq, from 15/10/2023 to 13/6/2024. A nonprobability convenience sample of 542 patients aged 0-18 years with CHD was collected by administering a constructed tool for the study. The data were collected from all Iraqi governorates, including the north, center, and south, as well as east and west countries. Result: The study shows the mean age of children was 2.2 ±9.2 years. The majority of children included were within infant age groups, almost equal in their sexes, giving girl to boy, 1.04:1. The age at screening and diagnosis of Echo was more than half in the first month, and the type of defect was Ventricular-septal-defect (VSD) and Tetralogy of Fallot (TOF). The study findings show that there is a statistically significant relationship between risk factors related to maternal medication history, including Folic acid Supplements. Maternal diseases such as Rubella, with CHD, and the highest recorded governorates for congenital heart defects are Baghdad, Mosul, and Diyala. Conclusions: The study concludes that most children included were within infant age groups, almost equal in their sexes, and the highest recorded governorates for congenital heart defects are Baghdad, Mosul, and Diyala. Also, the most frequent CHD is VSD and TOF, the history of maternal medication use, including folic acid supplements, and maternal diseases such as Rubella were significant factors in assessing the risk or outcome.